2022
DOI: 10.1136/bcr-2021-247470
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic metastasis of anal squamous cell carcinoma

Abstract: A 50-year-old woman was diagnosed with anal squamous cell carcinoma following a colonoscopy performed for positive test from the National Bowel Screening Programme. During the staging imaging, it was discovered to have a liver lesion that was atypical for metastasis. She underwent a segmental liver resection, and histopathology showed the liver lesion as a metastatic squamous cell carcinoma. We aim to discuss the incidence, presentation and management strategies for this rare hepatic metastasis of anal squamou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
(19 reference statements)
0
2
0
Order By: Relevance
“…In this analysis, we demonstrate that in 21 selected patients, median OS was improved by 1 year compared to historical controls and 30% were recurrence‐free at 5 years after metastasectomy. The data from this modest, multi‐institutional experience adds to existing knowledge established through case reports and case series with less than total 30 patients 1,4–8 and one analysis from the National Cancer Database 1 . Our study adds to existing evidence that patients with anal SCC metastases to the liver should be assessed on a case‐by‐case basis for potential resectability.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…In this analysis, we demonstrate that in 21 selected patients, median OS was improved by 1 year compared to historical controls and 30% were recurrence‐free at 5 years after metastasectomy. The data from this modest, multi‐institutional experience adds to existing knowledge established through case reports and case series with less than total 30 patients 1,4–8 and one analysis from the National Cancer Database 1 . Our study adds to existing evidence that patients with anal SCC metastases to the liver should be assessed on a case‐by‐case basis for potential resectability.…”
Section: Discussionmentioning
confidence: 75%
“…Previous research is limited to individual case reports or case series where liver resection was performed in conjunction with multimodal therapy (systemic chemotherapy, radiation). 4,5 One population-based study using the National Cancer Database found survival benefit in patients with liver metastasis undergoing metastasectomy, with an increase in OS from 16 to 34 months (p < 0.0001). 1 In high-volume centers, liver resection is already being pursued in highly selected patient populations.…”
mentioning
confidence: 99%